PENGARUH MEDIA SOSIAL TERHADAP MOTIVASI BELAJAR SISWA DI SMP NEGERI 12 KOTA TIDORE KEPULAUAN - Asnita Ode Samili; Syarifuddin Adjam; Fitriana Ibrahim; Jainudin Hasim (Universitas Khairun, 2024)
This article examines the use of social media in supporting the learning process at SMP Negeri 12 Tidore Islands. This research method is qualitative, data collection techniques are interviews, observation and documentation. The results of this research found that the use of social media really supports learning at SMP Negeri 12 Tidore Islands, students are very enthusiastic in collaborating on teaching materials with online media, students are more enthusiastic about following online tutorials, students find it easier to learn, teachers are providing education to students to use social media wisely, with social media, teachers and students can interact in learning activities anywhere and at any time, so they are not limited to space and time.